SUSTAINABILITY OF FAMILY BUSINESS: MILLENNIALS INTENTION TO STAY IN THE FAMILY BUSINESS AS THE RESULT OF STEWARDSHIP CLIMATE, MEDIATED BY SUCCESSOR'S TRUST AND SOCIOEMOTIONAL WEALTH - Riznika, Irzal; Kaihatu, Thomas Stefanus (Jurnal Aplikasi Manajemen, 2021)
This research studies the influence of stewardship on the intention to stay in the family business. Successor's trust and socioemotional wealth are also studied as mediator. The population in this research is Millennials that work in a family business and have prepared as a successor. Samples were taken purposively from family business members of KADIN East Java (Chamber of Commerce). The sample collected was 221. Data were analyzed with Andrew Hayes PROCESS model 4. The result shows that stewardship has a significant positive effect on the successor's trust, socioemotional wealth, and intention to stay. Successor's trust and socioemotional wealth have a significant positive effect on the intention to stay. Successor's trust and socioemotional wealth have a mediating effect on the relationship between stewardship and intention to stay. The findings contribute to the succession strategy in the family business, especially to make Millennials' successors willing to stay in the family business. The suggestion for future research is to test the effect on different cohorts as Generation Z or different family cultures.